2012
DOI: 10.15835/nsb437554
|View full text |Cite
|
Sign up to set email alerts
|

Improving Chilling Tolerance of Maize Seedlings under Cold Conditions by Spermine Application

Abstract: Low temperature is an important abiotic stress which reduces crops growth and productivity and causes physiological damages to cellular structures. The aim of this study was to investigate the probability of spermine application to improve chilling tolerance of maize under stress conditions. The treatments were included seed priming with spermine (30, 60 and 90 mg/l solutions) and normal and stress condition. Seed emergence was improved by spermine priming on both conditions and mean emergence time (MET) was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Reduced shoot and root growth of maize plants exposed to low temperatures has been attributed to severe oxidative damage induced by cold stress [13,29]. The different isoforms of SO as key enzyme for detoxification of free radicals, strongly depend on Zn, Mn, Cu, and Fe as cofactors and have been implicated in chilling tolerance of higher plants [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced shoot and root growth of maize plants exposed to low temperatures has been attributed to severe oxidative damage induced by cold stress [13,29]. The different isoforms of SO as key enzyme for detoxification of free radicals, strongly depend on Zn, Mn, Cu, and Fe as cofactors and have been implicated in chilling tolerance of higher plants [29].…”
Section: Discussionmentioning
confidence: 99%
“…Under favorable conditions, short cold periods can be tolerated and later compensated during plant development until final harvest. However, longer stress periods can easily induce irreversible damage already in the seedling stage [13].…”
Section: Introductionmentioning
confidence: 99%
“…The negative effects of suboptimal temperature on maize germination parameters and early seedling growth has been previously reported. Saeidnejad et al (2012) showed that low temperature decreased maize seed germination parameters, seedling emergence and growth. Low temperature had deleterious effect on membrane stability, relative water content, starch metabolism and antioxidant activities (Farooq et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that cold stress can reduce shoot and root growth of maize plants due to oxidative damage (Saeidnejad, Pouramir, & Naghizadeh, ). A clear reduction in growth of maize under cold stress was observed for both soils in this experiment (Figure ).…”
Section: Resultsmentioning
confidence: 99%